Cerebral blood flow velocity progressively decreases with increasing levels of verticalization in healthy adults. A cross-sectional study with an observational design - Deseoe, Julian; Schwarz, Anne; Pipping, Theodor; Lehmann, Aurelia; Veerbeek, Janne M.; Luft, Andreas R.; Wegener, Susanne; Globas, Christoph; Held, Jeremia P. O. (Frontiers in Neurology, 2023)
Background Autoregulation of the cerebral vasculature keeps brain perfusion stable over a range of systemic mean arterial pressures to ensure brain functioning, e.g., in different body positions. Verticalization, i.e., transfer from lying (0°) to upright (70°), which causes systemic blood pressure drop, would otherwise dramatically lower cerebral perfusion pressure inducing fainting. Understanding cerebral autoregulation is therefore a prerequisite to safe mobilization of patients in therapy. Aim We measured the impact of verticalization on cerebral blood flow velocity (CBFV) and systemic blood pressure (BP), heart rate (HR) and oxygen saturation in healthy individuals. Methods We measured CBFV in the middle cerebral artery (MCA) of the dominant hemisphere in 20 subjects using continuous transcranial doppler ultrasound (TCD). Subjects were verticalized at 0°, −5°, 15°, 30°, 45° and 70° for 3–5 min each, using a standardized Sara Combilizer chair. In addition, blood pressure, heart rate and oxygen saturation were continuously monitored. Results We show that CBFV progressively decreases in the MCA with increasing degrees of verticalization. Systolic and diastolic BP, as well as HR, show a compensatory increase during verticalization. Conclusion In healthy adults CBFV changes rapidly with changing levels of verticalization. The changes in the circulatory parameters are similar to results regarding classic orthostasis. Registration ClinicalTrials.gov, identifier: NCT04573114.